2021
DOI: 10.1177/20503121211017756
|View full text |Cite
|
Sign up to set email alerts
|

Rate control with intravenous diltiazem, verapamil, and metoprolol in acute atrial fibrillation with rapid ventricular rate

Abstract: Introduction: Diltiazem is a preferred agent for rate control in atrial fibrillation due to its quick onset, minimal side effects, and low cost. Due to its intermittent national shortage since February 2018, the utilization of intravenous metoprolol and verapamil has increased. This study investigated the effect of intravenous diltiazem, metoprolol, and verapamil on rate control in patients with atrial fibrillation with rapid ventricular rate. Methods: This study was a retrospective, single-center, cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…2 ). 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 These studies enrolled 1732 patients in emergency departments (thirteen studies) and intensive care unit settings (one study). These fourteen studies were pooled, as they each reported achievement of rate control target with diltiazem (n = 773) compared to metoprolol (n = 959) in patients with atrial fibrillation with rapid ventricular rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ). 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 These studies enrolled 1732 patients in emergency departments (thirteen studies) and intensive care unit settings (one study). These fourteen studies were pooled, as they each reported achievement of rate control target with diltiazem (n = 773) compared to metoprolol (n = 959) in patients with atrial fibrillation with rapid ventricular rate.…”
Section: Resultsmentioning
confidence: 99%
“…3 ). 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 18 , 20 Meta-analysis of outcomes of these twelve studies showed no significant difference in the occurrence of hypotension as an adverse event with diltiazem (n = 647) vs. metoprolol (n = 830) in patients with atrial fibrillation with rapid ventricular rate (odds ratio: 0.96; 95% CI: 0.61 to 1.52; p = 0.87); without significant heterogeneity (I 2 = 35%). Nine studies, including 1203 patients, reported the rate of bradycardia as an adverse event with diltiazem versus metoprolol ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nondihydropyridine calcium channel blockers (eg, verapamil, diltiazem), beta blockers, and adenosine are indicated to terminate AV node‐dependent PSVT when vagal maneuvers are ineffective 2,3 . Likewise, calcium channel blockers and beta blockers are often used to establish ventricular rate control during atrial‐based tachyarrhythmias by slowing conduction over the AV node 4,5 …”
Section: Figurementioning
confidence: 99%
“…2,3 Likewise, calcium channel blockers and beta blockers are often used to establish ventricular rate control during atrial-based tachyarrhythmias by slowing conduction over the AV node. 4,5 Etripamil, a fast-acting nondihydropyridine L-type calcium channel blocker, is a close structural analog of verapamil, modified by the addition of an ester group (Figure 1A). [6][7][8][9][10] According to an unpublished in vitro study of the incubation of etripamil in human whole blood, etripamil is rapidly and completely transformed to the stable and pharmacologically inactive metabolite MSP-2030 by blood esterases, indicating that hepatic metabolism is not a significant factor in the biotransformation of etripamil (Figure 1B, Figure S1).…”
mentioning
confidence: 99%